COVID-19 and cholera co-infection and comorbidity in Africa and Asia: a systematic review and meta-analysis - Olalekan Chris Akinsulie; Oluwagbemisola Oyin Olukogbe; Ibrahim Idris; Melina Joshi; Rhonda Williams; Roberta Koku; Sammuel Shahzad; Pius I. Babawale; Olamilekan Gabriel Banwo; Joy Olaoluwa Gbadegoye; Charles Egede Ugwu; Oluwole Fasakin; et al. (Journal of Global Health Economics and Policy)
# Background